Infecto-contagious diseases in day care centers: a systematic review - Sousa, Cícero V. L.; Alves, Beatriz C. A.; Perez, Matheus M.; Fonseca, Ricardo L. A.; Veiga, Glaucia R. L. da; Azzalis, Ligia A.; Junqueira, Virginia B. C.; Fonseca, Fernando L. A. (International Journal Of Community Medicine And Public Health, 2018)
Agglomeration and contact among children in day care centers has increased; however, this population has a high level of immunological immaturity, which makes it vulnerable to respiratory and gastrointestinal pathologies. This work aimed to identify the factors predisposing infecto-contagious diseases in day care centers. This is a systematic review of the literature carried out in the international database Pubmed, using the descriptors: Causality, Communicable Diseases, Child Day Care Centers. After adding the descriptors in the database, 79 papers were generated, however only eight fit the criteria established in this study. Day care centers are ideal environments for the development of diseases of the respiratory tract and otitis media, but may be environments that reduce the risk of acute lymphoblastic leukemia and neuroblastoma. There are still few mechanisms to prevent and control infections in these environments.